Targeting NK Cells for HIV-1 Treatment and Reservoir Clearance - Duan, Siqin; Liu, Shuwen (Frontiers in Immunology, 2022)
Combined antiretroviral therapy (cART) can inhibit the replication of human immunodeficiency virus type 1 (HIV-1) and reduce viral loads in the peripheral blood to undetectable levels. However, the presence of latent HIV-1 reservoirs prevents complete HIV-1 eradication. Several drugs and strategies targeting T cells are now in clinical trials, but their effectiveness in reducing viral reservoirs has been mixed. Interestingly, innate immune natural killer (NK) cells, which are promising targets for cancer therapy, also play an important role in HIV-1 infection. NK cells are a unique innate cell population with features of adaptive immunity that can regulate adaptive and innate immune cell populations; therefore, they can be exploited for HIV-1 immunotherapy and reservoir eradication. In this review, we highlight immunotherapy strategies for HIV infection that utilize the beneficial properties of NK cells.